Design and laboratory tests of flexible trailing edge demonstrators for wind turbine blades. Issue 2 (April 2023) - Pohl, Martin; Riemenschneider, Johannes
To increase the power yield, wind turbines have significantly grown in the last decades. Today, this growth is more and more limited by the weight of the structures and fatigue loads. To compensate these loads, especially flapwise root bending moments, trailing edge flaps can be used. They can change the lift of the blade with little delay to equalize the aerodynamic lift and by this reduce the fatigue amplitude. Such a trailing edge flap has been designed, developed, built and experimentally tested. It uses a flexible, morphing design to seal the entire mechanics against environmental influences, such as rain, dust, or insects. Therefore a design made from glass fiber reinforced plastics in combination with elastomer materials is used. In this paper the design process from the concept to two consecutive demonstrators is presented. Both are tested in the laboratory for their morphing characteristics.